The Influence of Relationship Marketing and Service Quality with Customer Satisfaction Mediation Variables on Customer Loyalty - Nur Aprilia Dwilianingsih; Rhian Indradewa (Quantitative Economics and Management Studies, 2022)
Customer loyalty is so important for a company to retain customers. Customer loyalty is worth to reduce competition between competitors. Customer loyalty can be influenced by relationship marketing, service quality, and customer satisfaction. So this study aims to see the effect of relationship marketing, service quality, customer satisfaction, and customer loyalty. The population of this study focuses on Indonesian Islamic Bank (BSI) customers, using purposive sampling. The sample is Indonesian Sharia Bank (BSI) customers in the Tangerang area as many as 230. This type of research is quantitative, with data collection by distributing questionnaires. The analytical method used is the Structural Equation Model (SEM-PLS) with the SMART PLS software program. This study aims to see the effect of relationship marketing, service quality, customer satisfaction, and customer loyalty. The results of the study conclude that relationship marketing and service quality have a positive effect on customer satisfaction and customer loyalty. Customer satisfaction as a mediating variable has a positive effect on customer loyalty. The implication of this research is the company order to increases customer loyalty by making customers feel satisfied through relationship marketing and the quality of services provided